Pengaruh Kosentrasi Asam Klorida (HCl) Terhadap Pembentukan Koagulat pada Kosentrat Protein Daun Pepaya (Carica papaya L.) Sebagai Bahan Pakan - Syaiful Bahri (Biocelebes, 2008)
Papaya (Carica papaya L.) leaf contain 21-23% gross protein from its dry weight. The analysed leaf taken from sixth-eighth leaf from apical. Papaya leaf was blend with water in 1:3 ratio until change as a pulp form. Papaya leaf protein was extracted by chloride acid solution in the different concentration. Complete Randomized Design was used with 4 treatment consist of: Y1 (papaya leaf pulp with added by HCl 0,002 M), Y2 (papaya leaf pulp with added by HCl 0,004 M), Y3 (papaya leaf pulp with added by HCl 0,006 M), and Y4 (papaya leaf pulp with added by HCl 0,008 M). The result of research showed that treatments giving the very significant effect (P  0,01) on the protein content and weight of papaya leaf concentrate coagulate. Meanwhile, no significant effect (P0,05) on the content of the dry weight of protein concentrate. Key words : Protein, Carica papaya L., Pakan